Peran Negara dalam Perlindungan Hak Komunal atas Ekspresi Budaya Tradisional ditinjau dari Hukum Internasional Dan Nasional - Enggriyeni, Dewi; Medina, Dayu (Nagari Law Review, 2024)
Traditional Cultural Expression (TCE) is a indigenous people’s Communal Intellectual Property (CIP), whose copyright is owned by the state. As author of copyright, the state has moral and economic rights. However, in the fact, indigenous people that preserve and guard TCE from generation to generation. This article was produced through normative juridical research, namely research carried out by analyzing secondary data in the form of primary, secondary and tertiary legal materials related to TCE. This research found that TCE as communal intellectual property based on the international regime is found in the WIPO and WIPO-IGCGRTKF drafts, while the national regime is found in Undang-Undang Hak Cipta Nomor 28 Tahun 2014, Undang-Undang Merek dan Indikasi Geografis Nomor 20 Tahun 2016 and Peraturan Pemerintah Nomor 56 Tahun 2022 tentang Kekayaan Intelektual Komunal. This regulation legitimizes the state as author of the copyright but ignores the rights of indigenous peoples on TCE. In Indonesia TCE’s legal protection consist of positive and defensive protection. The positive protection is found in Undang-Undang Hak Cipta Nomor 28 Tahun 2014 and defensive protection in Peraturan Pemerintah Nomor 56 Tahun 2022 tentang Kekayaan Intelektual Komunal. Therefore, sui generis legal regulations are needed to recognition of indigenous peoples’s copyright on TCE.